Climate influence on future suitability of high-altitude wetlands in two natural protected areas from the Central Andes of Argentina - Vento, Barbara (2024)
Climate conditions have a strong influence on the distribution of many natural communities; thus, the influence of global climate change may alter ecosystems. High-altitude wetlands in the Central Andes of Argentina (CAA) provide relevant ecosystem benefits and promote human activities. However, a degradation of Andean wetlands has been observed and documented in the last decades. Projecting the impacts of climate change on future distribution of wetlands is an essential subject in ecological studies. In this work, the present and future suitability for wetland systems in a pristine section of the CAA using spatial distribution modeling under low and high-emission scenarios are explored. The studied wetlands are strongly driven by bioclimatic variables such as mean annual temperature, precipitation, and its seasonality. Projections show that most of the currently occupied areas will modify under future climate conditions. Changes in temperature and precipitation patterns will decrease the potential suitability in low elevation areas for the next decades for the species inhabiting there, especially south of 29 °S. Additionally, future warmer climatic conditions, greater temperature variability, and reduction in precipitation would probably affect the snow cover and the available water supply which are key limiting factors for the distribution of Andean wetlands. This research is a contribution to understanding possible effects of climate change on high-altitude ecosystems. Mitigation measures for conservation of wetlands in CAA are immediately required to compensate for the impact of climate change under future environmental conditions.